Occupational skin dermatoses among health care workers: A review of adverse skin reactions to personal protective equipment - Agnes Rosarina Prita Sari; Yudha Nur Patria; Olivia Roselin Wiguna; Hardyanto Soebono; Sri Awalia Febriana (PAGEPress Publications, 2022)
Occupational skin-related problems include dermatoses caused by agents in the working environment. For health care workers, these occupational dermatoses could be due to usage of personal protective equipment (PPE), such as gloves, masks, goggles, and other protective equipment. These PPE contribute to both allergic and irritant contact dermatitis. This review summarized the skin damage after PPE usage and hand hygiene protocol. Recommendations should be established to prevent these occupational dermatoses from PPE usage.